Postnatal Sexual Concerns Regarding the Selection of Delivery Mode among Iranian Women: A Qualitative Content Analysis - Zahra Abbaspoor; Lida Moghaddam-Banaem; Fazlollah Ahmadi; Anoshirvan Kazemnejad Lili (Mashhad University of Medical Sciences, 2016)
Background & aim: Several factors influence the choice of cesarean section and its increasing rate among pregnant women. It seems that sexual satisfaction after childbirth plays a pivotal role in the selection of delivery mode. This study aimed to describe the experiences of pregnant women regarding postnatal sexual concerns and delivery mode selection. Methods:This conventional qualitative content analysis was based on the study by Graneheim & Lundman (2004). Sample population consisted of 18 pregnant women undergoing natural vaginal delivery (NVD) or elective cesarean section (CS) at term in three hospitals and two healthcare centers of Tehran, Iran. Data collection and analysis were performed concurrently, and interviews continued until data saturation was achieved. Results: In this study, the main extracted theme was "decision-making influenced by socio-cultural childbirth beliefs." One of the main categories comprising the content of the interviews was "meeting the sexual satisfaction of spouse" with subcategories of "spouse dissatisfaction after NVD" and "preserved sexual satisfaction after CS." The other category was "preserving the original shape of genital organs" with subcategories of "necessity of cosmetic surgery after NVD" and "maintaining an intact genital system after CS." Conclusion: According to the results of this study, sexual attitudes and beliefs in the Iranian society are essentially involved in women's preference of CS over NVD. Choice of CS by pregnant women is often influenced by the opinion of the spouse, family members, peers, and friends. Therefore, it is recommended that the knowledge of couples in this regard be enhanced through related educational programs.